Pengaruh Strategi Kepala Madrasah dalam Pembelajaran Berbasis Information Technology Terhadap Peningkatan School Brand Image di Madrasah Interaktif Mimha Bandung - Salma Nirmala; Mustaqim Mustaqim; Nina Nurmila (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study discusses the influence of the madrasah principal's strategy in information technology-based learning on improving the school brand image at Madrasah Interactive MIMHa Bandung. The madrasah principal plays an important role in integrating information technology to improve the quality of learning and the attractiveness of the school. This study aims to describe the madrasah principal's strategy in information technology-based learning, explain the improvement of the school's image, and analyze the influence between the two. The method used is a survey with an ex post facto approach, involving 33 teachers as respondents. Data were collected through questionnaires, documentation, and interviews, then analyzed quantitatively. Based on the results of the study, the madrasah principal's strategy in information technology-based learning has an influence of 43.7% on improving the school brand image, while the rest is influenced by other factors. This means that the better the technology-based learning strategy implemented by the madrasah principal, the more positive the madrasah's image in the eyes of the public. This study recommends the development of innovative technology-based strategies to strengthen the competitiveness and reputation of educational institutions.